POLITICAL CORRECTNESS IN POLITICAL DISCOURSE: THEORY OF IDEOLOGICAL ASPECT - Yuliia G. Karachun; Nataliia V. Davydenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article aims to highlight the ideological aspect of functioning politically correct vocabulary in today’s political discourse. Realization of the set goal requires solving the following objectives: 1) to expand scholarly ideas about the interpretation of the linguistic phenomenon of political correctness as sociocultural and linguistic-behavioral ideology in political discourse; 2) based on the introduction of the concept “ideologeme”, to consider the classification of politically correct lexical units, used in political discourse. The study employs general scientific methods (analysis, generalization, systematization of scholarly literature on the issue under consideration), and special linguistic methods (method of distributional analysis, used to highlight the main semantic groups of politically correct vocabulary; elements of the component analysis, necessary to identify components of the meaning of politically correct vocabulary; method of linguostylistic analysis, used to study the functional features of politically correct vocabulary based on ideology). The study emphesizes that the phenomenon of political correctness can be considered as a set of linguistic and discursive components of the organization of the ideological life of modern society. It is able to ensure the creation of a system of values, the worldview, and in general, it involves the construction of reality. It also contributes to the dissemination and imposition of an opinion on one or another issue in society, mostly within the framework of political discourse. Political correctness deals with a situation in society where implicit rules of decency direct the ways of behavior in interactions between people of different races, genders, religions, and other potentially charged groups. It seems that political correctness in political discourse concerns all those areas where the interests of different groups of society collide on the issue of what is considered true or false, and who is considered “friend” or “stranger”. Political correctness as an ideology offers a polar view on social life, highlighting in it “good” (“right”) and “evil” (“bad”). Consequently, at the most abstract level, there are concepts that define the basic values of political correctness, as well as their “antipodes,” i.e., undesirable, unacceptable phenomena and attitudes that must be eradicated from social life (e.g., tolerant / intolerant, inclusive / exclusive). In general, it can be presented as a “good – evil” model of social life, which works and effectively serves the ideology of political correctness. Admittedly, the structure of the language of political correctness is not as homogeneous as it is commonly believed. Two broad layers of politically correct lexis that perform qualitatively different roles are considered: politically correct vocabulary, which includes the “acceptable” names of sociocultural phenomena, and politically correct ideologemes that are used to directly form a politically correct worldview. Ideologemes, as a result of the interaction of language and ideology, represent the optimal means for establishing the dominant worldview in the country, influence the transformation of the addressee’s already existing political worldview, explicitly or implicitly represent the basic ideological and value attitudes of a society. If politically correct vocabulary itself is an example of the “acceptable” language concerning different matters of life, then the ideologemes of political correctness set standards for assessing heterogeneous sociocultural phenomena. In turn, the attitudes and principles embedded in the ideologemes are implemented in the creation of politically correct vocabulary. Thus, ideologemes form the core of the linguistic representation of the ideology of political correctness. Their most common word-formation models involve exploiting the suffix -ism, the -free and -phobia components, the words “bias” and “sensitivity”. It can be argued that the ideologeme is a characteristic element of the global political context, since it is a kind of reference to a particular era, its meaning is detached from the direct meanings of the lexical units that make it up. An adequate understanding of the ideologeme is p